Flexible thin SiC fiber fabrics using carbon nanotube modification for improving electromagnetic shielding properties. (15th August 2016) - Liu, Xiaofei; Zhang, Litong; Yin, Xiaowei; Ye, Fang; Liu, Yongsheng; Cheng, Laifei
Abstract: In order to obtain a flexible electromagnetic shielding materials with thin thickness and low electromagnetic wave reflection, pyrolytic carbon (PyC) and carbon nanotube (CNT) were in situ formed on the surface of SiC fiber fabrics (SiCf, with the thickness of 0.34 mm) through chemical vapor deposition and catalytic chemical vapor deposition to form PyC-SiCf and CNT-SiCf fabrics, separately. CNT-SiCf can maintain the flexibility of SiC fiber fabrics because of the high aspect ratio of CNT, but PyC-SiCf fabrics can not. CNT-SiCf had much lower electrical conductivity than PyC-SiCf because of their higher contact electrical resistance. At the same loading, CNT-SiCf and PyC-SiCf could obtain higher EMI SE (≥ 15 dB), but CNT-SiCf had lower reflection loss (≤ 6 dB) than PyC-SiCf (≥ 8 dB) because CNT-SiCf had much lower electrical conductivity and larger interface area than PyC-SiCf . Graphical abstract: Highlights: SiC fiber fabrics modified by CNT have the features of thin thickness, flexibility and highly absorbing properties. CNT-SiCf had lower electrical conductivity because of their higher contact electrical resistance. CNT-SiCf could obtain higher EMI SE (≥ 15 dB) and lower reflection loss (≤ 6 dB).